2017
DOI: 10.1103/physrevlett.119.268102
|View full text |Cite
|
Sign up to set email alerts
|

One-Parameter Scaling Theory for DNA Extension in a Nanochannel

Abstract: Experiments measuring DNA extension in nanochannels are at odds with even the most basic predictions of current scaling arguments for the conformations of confined semiflexible polymers such as DNA. We show that a theory based on a weakly self-avoiding, one-dimensional “telegraph” process collapses experimental data and simulation results onto a single master curve throughout the experimentally relevant region of parameter space and explains the mechanisms at play.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(85 citation statements)
references
References 49 publications
1
83
1
Order By: Relevance
“…Werner et al developed a one-parameter theoretical prediction for estimating the physical properties of DNA for square nanochannels in this size range. [21] In the Supporting Information, we demonstrate how this prediction can be used to estimate the persistence length of DNA, with and without aS bound, by approximating the rectangular channel size by its geometric mean (Supporting Information data analysis, Figures S2 and S3). The conclusion from this analysis is that the persistence length gradually increases from around 70 nm for naked DNA to around 90 nm for DNA with 40 μm aS added (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Werner et al developed a one-parameter theoretical prediction for estimating the physical properties of DNA for square nanochannels in this size range. [21] In the Supporting Information, we demonstrate how this prediction can be used to estimate the persistence length of DNA, with and without aS bound, by approximating the rectangular channel size by its geometric mean (Supporting Information data analysis, Figures S2 and S3). The conclusion from this analysis is that the persistence length gradually increases from around 70 nm for naked DNA to around 90 nm for DNA with 40 μm aS added (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, if the DNA has contour length L and is in a linear (unfolded) state in the nanochannel, the extension X U is given as X U = α U L. In the extended de Gennes regime, the value of the prefactor α U is known exactly, [34] and for stronger confinement the values were computed in Ref. [40]. In the circular (folded) state, the molecule has extension X F = α F L 2 , see Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[29,30,31,34] Since the channel width is of the order of the persistence length of the DNA molecule, our system is in fact in between these two regimes. However, it was recently shown that the underlying physics is the same in the different regimes, [40] only prefactors in the estimates of forces and mobilities may differ. In particular, the force f is independent of the extension, and the mobility is inversely proportional to the extension.…”
Section: B U L W U O O J K M C X 3 a C Z + D C J T T G B P R Q A G J mentioning
confidence: 99%
See 1 more Smart Citation
“…To compute the distribution of label spacings along the channel axis, we use the model derived in Ref. 32, projecting the three-dimensional DNA configurations x(t) onto the channel axis x. The model consists of two parts: an ideal correlated random walk, and a bias that takes into account self avoidance.…”
Section: Telegraph Modelmentioning
confidence: 99%